Assessment of Fire Hazard on the Readymade Garment Industry in Chittagong City, Bangladesh: A geo-spatial analysis of CEPZ and Baizid Industrial Hub - Shahidul Islam; Rafion Islam Roman (Research Centre of Inorganic Materials and Complexs, 2019)
The Readymade Garments (RMG) industries are in Bangladesh is the largest contributor to the national export earnings and second largest in GDP of the country. Starting from the late Seventies as minor as well as non-traditional sector with a negligible of exporting, the RMG sector has dramatically grown up a geometric progression over the few decades. Although the country has a glorious history of textile, cloths and clothing’s from the ancient period of time. At present, about 75% of the total exports of the country having from this sector and one of the principle key points of employment. Over the preceding decade, fire and fire hazard is the continual problem in the country’s readymade garments industries. Only in 2012 about 169 people died and huge people are injured because of fire hazards in RMGs. Considering this as a crucial problem, the study was carried out a geo-spatial analysis on Chittagong Export Processing Zone (CEPZ) and Baizid Industrial hub of Chittagong city, Bangladesh. The study was mainly done by primary field survey while secondary sources were also used in comparing and basement of analysis. There are two types of parameters (Hard and Soft Parameters) generally used to assess the fire hazard of readymade garments. The research has been done by adopting the soft parameter, as exit door locked, emergency exit in the factory, fire extinguisher etc. The Fire Risk Index has been developed on the basis of 19 soft parameters. In Chittagong EPZ area 25 garments factories have been surveyed instantly to observe the current status of fire risk for the lack of 19 parameters. Results show that in CEPZ area for 19 parameters the mean safety is 90.45% or 9.55% deviation from the standard. On the contrary, the average condition of 19 parameters is 80.29% fluctuation from the benchmark in the Baizid Industrial area though it is considered as good condition but nearest to the average. Electric short circuit is the prime cause of fire in CEPZ area and also in Baizid industrial hub. At the eleventh hour, it is found from the study that about 80% garments in Baizid Industrial area under in good condition which is (10-20) % deviation from ideal case. On the other hand in CEPZ area about 80% garments are fallen excellent condition, it is only 8% seen in Baizid area. The study also reveals that there is no garments in both area which is in poor or average condition or vulnerable to fire hazards but in Baizid it is about 20% garments are fallen average condition or nearly vulnerable. Before conducting the study, it is seemed that it will be found the garments will be more vulnerable to fire hazards but at the end of the day it is proved as erroneous, for the recurrence of fire hazards in the last few years they have raised the magnitude of fire safety in almost every cases and now the garments are more secured in case of fire hazards.